Increased Temperature and Discharge Influence Overwinter Growth and Survival of Juvenile Salmonids in a Hydropeaking River : Simulating Effects of Climate Change Using Individual-Based Modelling - Watz, Johan; Schill, Joel; Addo, Louis; Piccolo, John; Hajiesmaeili, Mahboobeh (Fishes, 2023)
Climate change causes warming of rivers and may increase discharge, particularly during winter. Downstream of hydropower plants, fluctuating water temperature and flow create dynamic overwintering conditions for juvenile salmonids. We used inSTREAM 7.2-SD to simulate the effects of increased temperature (+2 & DEG;C) and discharge (+10%) on the overwinter growth and mortality of one-summer- and two-summer-old Atlantic salmon and brown trout in a river with a hydropeaking flow regime in a 2 x 2 design with replicated simulations. Water temperature had a major positive relationship with growth for both species and year classes, whereas increased flow alone had no major general effect on overwinter growth. For one-summer-old trout experiencing the high temperature regime, however, increased flow resulted in reduced growth. There were no major effects from temperature and flow on the survival rate of the two-summer-old fishes. On the other hand, there were significant interaction effects for the one-summer-olds, indicating that the effect of flow depended on temperature. For one-summer-old salmon, high flow resulted in increased survival in the low temperature regime, whereas it resulted in reduced survival in high temperature. In contrast, for one-summer-old trout, high flow resulted in reduced survival in the low temperature regime and increased survival in the high temperature. Different hydropower operation alternatives may interact with warming, affecting the relative competitive abilities of stream salmonids. Ecological models that predict the effects of different environmental conditions, such as temperature and flow regimes, may offer insight into such effects when in situ experiments are not feasible.